Girls in tears - Wilson, Jacqueline; Sharratt, Nick (London Random House Children's Company, 2006)
Ten-year-old Mandy must endure torment from three nasty bullies in school, but she finds solace in a new friendship with an older girl.
Keywords: Fiction; England -- Fiction